Review of the Mechanism of Tooth Whitening. Issue 5 (13th May 2015) - Kwon, So Ran; Wertz, Philip W.; Paravina, Rade
Abstract Purpose This review integrated the current literature on diffusion of whitening agents, their interactions with stain molecules, and changes to the surface, with the aim of establishing a better understanding of the mechanism underlying tooth whitening. Materials and Methods An electronic PubMed database search, with combinations of the following terms was performed: Tooth Bleaching, Tooth Bleaching Agent, Hydrogen Peroxide, Pharmacokinetics, Tooth Permeability, Oxidation‐Reduction, Tooth Demineralization, and Color. Results Tooth whitening is a dynamic process that involves diffusion of the whitening material to interact with stain molecules and also involves micromorphologic alterations on the surface and changes within the tooth that affect its optical properties. The interaction seems not to be limited to stain molecules, but rather an affinity‐based interaction process that also accompanies effects on sound enamel and dentin structures. Conclusions This review underlines that supervision by dental health professionals as recommended by the American Dental Association (ADA) Council on Scientific Affairs is critical to achieving a successful and safe whitening outcome. Clinical Significance The mechanism that underlies tooth whitening with the use of peroxide‐based materials is a complex phenomenon encompassing diffusion, interaction, and surfaces changes within the tooth. Therefore, supervision by dental health professionals as recommended by the ADA Council on Scientific Affairs is imperative to achieve a successful and safe whitening outcome.